2010
DOI: 10.1182/blood-2010-04-279083
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent BRAF mutations in Langerhans cell histiocytosis

Abstract: Langerhans cell histiocytosis (LCH) has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
864
11
39

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,061 publications
(948 citation statements)
references
References 19 publications
34
864
11
39
Order By: Relevance
“…Inhibition of BRAF activation by vemurafenib improves the survival of patients with metastatic melanomas carrying the BRAFV600E mutation [51]. BRAFV600E mutations were reported in patients with LCH in 2010 [52], and we therefore screened patients with other types of histiocytosis for this mutation. We used pyrosequencing to test DNA, from paraffin-embedded samples from 127 patients with histiocytoses, for BRAFV600 mutations, and reassessed histology findings [53••].…”
Section: Braf Inhibition As An Alternative To Ifnα For Ecd Patients Cmentioning
confidence: 99%
“…Inhibition of BRAF activation by vemurafenib improves the survival of patients with metastatic melanomas carrying the BRAFV600E mutation [51]. BRAFV600E mutations were reported in patients with LCH in 2010 [52], and we therefore screened patients with other types of histiocytosis for this mutation. We used pyrosequencing to test DNA, from paraffin-embedded samples from 127 patients with histiocytoses, for BRAFV600 mutations, and reassessed histology findings [53••].…”
Section: Braf Inhibition As An Alternative To Ifnα For Ecd Patients Cmentioning
confidence: 99%
“…8 Young individuals with LC histiocytosis are reportedly more commonly positive for BRAF V600E. 8 The two patients tested in this study were of advanced age (69 and 80 years of age). All of the leukemias in this study were of ambiguous lineage or acute myeloid leukemia that expressed T-cell antigens.…”
Section: Discussionmentioning
confidence: 83%
“…FISH was performed on a lymph node of one patient who had a trisomy 21 leukemic clone. As BRAF mutations occur in a significant percentage of LC histiocytosis, 8 BRAF V600E testing was performed in three cases by real-time polymerase chain reaction (RT-PCR). DNA was extracted from formalin-fixed, paraffin-embedded tissue (two cases) or B5-fixed tissue (one case) using the DNeasy blood and tissue kit, and then diluted to a DNA concentration of 66.7 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies have highlighted the role of the RAS/RAF/ERK (MAPK) pathway in the pathogenesis of several histiocytic disorders, although few cases of RDD have been evaluated [5][6][7][8][9]31]. The RAS/RAF/ERK (MAPK) pathway is involved in various cellular functions including cellular proliferation, differentiation, and migration; mutation of genes involved in this pathway has been implicated in oncogenesis [32].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of RDD is very poorly understood. Recent studies have shown frequent BRAF V600E mutations in Langerhans cell histiocytosis (LCH) [5,6], Erdheim-Chester disease (ECD) [7], histiocytic sarcoma [8], and follicular dendritic cell sarcoma [8]. Further, NRAS, KRAS, and PIK3CA activating mutations have also been shown in ECD [6,9], highlighting the emerging importance of the RAF/MEK/ERK pathway in some histiocytic disorders.…”
Section: Introductionmentioning
confidence: 99%